Fisiologia e bioquímica de plantas da família Melastomataceae, Estação Ecológica do Panga, Uberlândia, MG - Teixeira, Walquíria Fernanda (2013)
CHAPTER I: Studies related to the germination of native species from Cerrado have assumed an important role due to the concern about the fragmentation of this biome. One consequence of fragmentation is the dryness of palm swamps that are being occupied by cerrado species, which makes the sourounnding an environment available for the transition to a new occupation. Thus, studies of seed germination in species that are participating in the occupation, become relevant because they contribute to restoration projects and conservation of the ecosystem. With this focus, the present study aimed to assess the intraspecific variability of seed germination of two species of Melastomataceae, collected in the cerradopalm swamp transition and cerrado stricto sensu in Central Brazil. For this, seeds were collected in the Panga Ecological Station, located in the town of Uberlândia, Minas Gerais, in December 2011. Two experiments were conducted in a completely randomized design, with seeds of six Miconia albicans and M. fallax individuals. Tests were performed in a biochemical oxygen demand (B.O.D.) type germination chamber, and data collection was conducted every 24 hours, observing the protrusion of the embryo. The seeds of M. albicans collected in the cerrado-palm swamp transition showed intraspecific variability for a greater number of features, when compared to those from cerrado stricto sensu, but in both collection environments a low germination percentage was observed, and values between 0% and 26% were found for the cerrado-palm swamp transition and between 0% and 33% for cerrado stricto sensu. On the other hand, the seeds of M. fallax showed intraspecific variability for a greater number of features in seeds from cerrado stricto sensu (germination from 21.5% to 84.5% and t between 11 and 14.5 days). The variance partition, obtained through hierarchical analysis, showed that the seed germination values of M. albicans and M. fallax are not affected by the collection site, and most of them are affected by the experimental waste. For both species, the highest percentage of germinability variation was attributed to differences between the individuals under study. This shows that the occupation of the dryed area of the palm swamp is relatively recent and, therefore the species are maintaining the same standard of germination in both places. CHAPTER II: The Melastomataceae family has been the focus of several studies, mainly due to its importance in Cerrado. One of the main characters of several species of this family is the aluminum accumulation. However, the role of this element on Melastomataceae species is unknown. Thus, this study aimed to evaluate the effect of aluminum on the Miconia albicans and M. fallax seed germination, collected in the cerrado-palm swamp transition and in cerrado stricto sensu. Seeds were select of individuals with a better germination potential, based in the initial germination tests. The two experiments were carried out under a completely randomized design, using aluminum doses as treatments (0, 5, 10, 20, 40, 80, and 160 mg L-1) and two environments (cerrado-palm swamp transition and cerrado stricto sensu), withfour replications (25 seeds each one). The results showed that M. albicans seeds, obtained from the cerrado-palm swamp transition had a higher germination capacity at 0 mg L-1 of Al (54%). Moreover, seeds from cerrado stricto sensu showed no significant differences in the application of aluminum rates (values between 9 and 18%), however, these seeds showed a longer mean germination time at low aluminum doses (0, 5 and 10 mg L-1, with values 14.71; 16.19 and 15.18 days, respectively), in relation tothe seedsfrom cerrado-palm swamp transition. M. fallax seeds presented different behavior,, although some aluminum rates have changed some aspects of the germination process, compared to the control treatment. The decrease in germination of M. albicans seeds from the cerrado-palm swamp transition may be related to the presence of aluminum in seeds. Probably the seeds used in this work could contain considerable amounts of this element, which has the addition of toxic aluminum. On the other hand, reducing the start time of seed germination of M. fallax from the cerrado-palm swamp transition, when subjected to doses of aluminum can be related to the adaptation of these plants to high concentrations of the element in the environment. CHAPTER III: The production of free radicals in plants has been the focus of several studies, particularly those which aim at quantifying the effect of a certain stress, that can be caused by biotic or abiotic factors. However, most of the works is performed with cultivated species, and few are developed with forest species. Some plants, such as Miconia albicans and M. fallax, can occur in environments with contrasting edaphoclimatic features. However, little is known about what features allow these plants to survive in so different environments. Therefore, this study aimed to evaluate physiological and biochemical features of plants of the Melastomataceae family occurring in the cerrado-palm swampy transition and cerrado stricto sensu. For this, leave samples of Miconia albicans e M. fallax were collected at the Panga Ecological Station, located in the town of Uberlândia, Minas Gerais, Brazil. Through the samples, the activity of the catalase, peroxidase, superoxide dismutase, and nitrate reductase enzymes were determined, and the chlorophyll, carotenoids, and lipid peroxidation were also quantified. The photosynthetic and transpiration activity of plants were also evaluated. All analyzes were conducted throughout the day (8 a.m., 10 a.m., 12 p.m., 2 p.m., and 4 p.m.) and in three seasons of the year. The soil from the study sites, in addition to irradiance, temperature, and air humidity were also measured. The data obtained were compared by means of confidence intervals with a significance level at 0.05. The results showed that, at the end of the rainy season, the plants from cerrado-palm swampy transition present high activity of the peroxidase enzyme compared to plants of cerrado stricto sensu. At the beginning of the dry season, the nitrate reductase enzyme showed high activity in M. albicans from cerrado-palm swampy transition (7.47 μg N-NO2 g-1 fresh weight h-1). The photosynthetically active radiation data show high values in the cerrado palm swampy transition (1140.6 W m-2). At the end of the dry season, the metabolism of plants decreased, making it more difficult to detect differences between environments and between collection times. The two evaluated species showed high levels of aluminium in leaves (4134e 10747 mg kg-1 in M. albicans and M. fallax), in all collection environments. Regarding the collection times, there was a high variation in the enzyme activity among the sampled individuals, something that made the activity from following a pattern, making it more difficult to determine the enzyme activity peaks. CHAPTER IV: Microlicia fasciculata in the Panga Ecological Station is restricted to areas of palm swamp, subject to various environments motification in recent years, particularly with respect to dryness, which may put it inrisk of local extinction. Furthermore, the cerrado has high concentrations of aluminum in the soil considered toxic to many crops. Faced with these characteristics, it is relevant to the study of this species, since these studies will help in understanding their ability to survive in these environments. In addition, studies related to germination and biochemical species are rare. Therefore, this study aimed to (1) assess the intraspecific variability of seed germination, (2) study the effect of aluminum on the germination and (3) assess the physiology and biochemistry of plants of this species for enzymatic activity related to the preservation of menbranes. For this, seeds were collected in December 2011, used in two experiments, each in a completely randomized design. The first seeds were used in 25 individuals, to evaluate the intraspecific variabilidaty for germination. The test was conducted with three replications of 50 seeds for each individual. In the second experiment was evaluated the effect of aluminum doses in germination (0, 5, 10, 20, 40, 80 and 160 mg L-1), with four replicates of 50 seeds for each dose. Biochemical analysis of leaves collected at different times of the year were also carried out and the data were compared by means of confidence intervals. The results showed the presence of high intraspecific variability for germinability (6 to 30%) and coefficient of variation of the germination time (10.22 and 29.75%). Seed germination was slow (0.08 ≤ v ≤ 0.11 days-1) and asynchronous (0.11 ≤ Z ≤ 0.38). These characteristics ensure the survival of the species in these unstable environments, especially in relation to volume of water that accumulates in the rainy season and a decrease in the dry or the dryness caused by human actions. Aluminum provided decrease in seed germination, with values between 5.5 and 8.0% for doses between 20 and 80 mg L-1, while without aluminum treatment yielded a 19% germination. This may be related to the presence of aluminum in the seeds, once the species is an accumulator of aluminum. Plants of the species in their natural environment showed variation in enzyme activity during the day, and the enzyme peroxidase and catalase had their eve its peak activity at noon in end of rainy season and the dry season. Thus, plants can maintain the level of lipid peroxidation stable throughout the day ensuring their survival.